Research on Curing Water Demand of Cementing Material System Based on Hydration Characteristics - Wang Yao (MDPI AG, 2021)
The performance of cover concrete is acknowledged as a major factor governing the degradation of concrete structures. Curing plays a vital role in the development of concrete durability. The effects of different water-binder ratios and mineral admixtures on the curing water demand of concrete were studied by the surface water absorption test. Combined with the characteristics of the hydration heat and chemically bound water of the composition cementing material system, the law of variation for curing water demand was analyzed. The results show that the addition of mineral admixtures can reduce the early hydration rate and hydration exothermic characteristics, and the hydration degree decreases with the increase of mineral admixtures. Due to the filling effect and active effect, the addition of fly ash (FA) and ground granulated blast slag (GGBS) reduces the curing water demand. The curing water demand of cover concrete decreases with the increase of mineral admixture content, and the curing water demand of pure water is the maximum and that of mix FA and GGBS is the minimum. Moreover, there is a strong correlation between the cumulative curing water demand and the chemically bound water content, indicating that the power of water migration mainly comes from the hydration activity of the cementing material system. The results provide a theoretical basis for the fine control of a concrete curing system.